Maxillary tuberosity fracture and ophthalmologic complications following removal of maxillary third molar. (17th March 2016) - Baba, J.; Iwai, T.; Endo, H.; Aoki, N.; Tohnai, I.
Abstract: Third molar removal is one of the most common procedures performed by dentists and oral surgeons. Removal of maxillary third molar is associated with a lower rate of complication compared to the mandible, and maxillary tuberosity fracture or ophthalmologic complications after removal of maxillary third molar are very rare. We report maxillary tuberosity fracture and ophthalmologic complications following removal of maxillary third molar. A 35‐year‐old female underwent removal of left maxillary third molar at private dental clinic. Following the complete extraction, excessive haemorrhage occurred and maxillary tuberosity fracture was seen and the patient was brought by ambulance to our hospital. The bleeding was controlled by vacuum‐formed splint and nasal packing. Computed tomography revealed that lateral maxillary tuberosity and posterior wall of the maxillary sinus was defect and there was a slight intraorbital haematoma via the inferior orbital fissure as well as with extension in the maxillary sinus and adjacent spaces such as buccal, masticator, pterygomaxillary and infratemporal spaces. Because an ophthalmologist noted only slight diplopia in lateral gaze without abnormal signs in other examinations and nasal and oral bleeding were controlled, the surgical treatment was not required. The patient was immediately hospitalised for close observation. Intravenous antibiotics and steroids were administered. Because swelling of the cheek and buccal mucosa was gradually decreasing without further haemorrhage, the patient was discharged 4 days after the extraction. The diplopia was recovered completely 11 days after the extraction.